2022
DOI: 10.6027/r2022:1.1403-2503
|View full text |Cite
|
Sign up to set email alerts
|

Essential rural services in the Nordic Region – Challenges and opportunities

Abstract: The objective of this knowledge overview of the project “Service provision and access to services in Nordic rural areas – secure, trusted and for all ages” is to analyse how essential service needs for different types of societal groups and ruralities can be understood and defined, and how solutions to rural service provision challenges can be organised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(37 citation statements)
references
References 36 publications
1
32
0
2
Order By: Relevance
“…This report presents results based on in-depth field work in eight case studies of rural areas identified as having high access to services or as good examples in their national and regional context: Lolland, Suðuroy, Kinnula, Avannaata, Múlaþing, Herøy, Vimmerby and Geta. The aim of the field work has been to investigate service provision and validate the results of a research and policy review focusing on Nordic rural areas (Slätmo et al 2022). The investigations presented in this report focus on the following questions:…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This report presents results based on in-depth field work in eight case studies of rural areas identified as having high access to services or as good examples in their national and regional context: Lolland, Suðuroy, Kinnula, Avannaata, Múlaþing, Herøy, Vimmerby and Geta. The aim of the field work has been to investigate service provision and validate the results of a research and policy review focusing on Nordic rural areas (Slätmo et al 2022). The investigations presented in this report focus on the following questions:…”
Section: Discussionmentioning
confidence: 99%
“…Denna rapport presenterar resultatet av ett fördjupat fältarbete i åtta fallstudier på landsbygder som identifierats ha hög tillgång till services eller som skulle kunna utgöra goda exempel i deras nationella och regionala sammanhang: Lolland, Suðuroy, Kinnula, Avannaata, Múlaþing, Herøy, Vimmerby, Geta. Syftet med fältarbetet har varit att undersöka försörjningen av services och validera resultaten från en forsknings-och policyöversikt med fokus på nordiska landsbygder (Slätmo et al 2022). Den studie som presenteras i denna rapport fokuserar på frågorna:…”
Section: Sammanfattningunclassified
See 3 more Smart Citations